Effect of infusion on fluoride concentration in various chinese tea - Wong, Win Ni; A.R. Suriah (Universiti Kebangsaan Malaysia, 2010)
The fluoride content in infusions of commercially available black tea, oolong tea, green tea, white tea and bata tea was determined via fluoride ion selective electrode method. Two methods of infusion were carried out: continuous infusion and repeated infusion. In continuous infusion, black tea yielded the highest concentration of fluoride, which ranged between 0.929±0.053 mg/L and 3.746±0.028 mg/L. Fluoride detected in brick tea ranged from 1.099±0.046 mg/L to 2.398±0.006 mg/L. The dissolvable fluoride for oolong tea, green tea, and white tea were ranged from 0.584±0.080 mg/L to 1.255±0.044 mg/L, 0.624±0.088 mg/L to 1.838±0.062 mg/L and 0.571±0.027 mg/L to 1.845±0.017 mg/L, respectively. The cumulative fluoride contents in repeated infusion were higher than those prepared by continuous infusion for all types of tea. Results of the study indicate that there was a wide range of fluoride content with different types of tea and methods of infusion. Because excessive intake of fluoride can cause dental and skeletal fluorosis, it is necessary for the government or international organization to establish a standard of fluoride content in tea commodities in order to protect the consumers against health hazards.